Physiological and metabolic analyses reveal the proline-mediated flowering delay mechanism in Prunus persica - Park, Yeonju; Muthuramalingam, Pandiyan; Jeong, Jae Hoon; Kim, Seung Heui; Shin, Hyunsuk (Frontiers in Plant Science, 2024)
Peaches are susceptible to various environmental stresses. Particularly in late spring, freezing temperatures can damage peaches and consequently, affect their productivity. Therefore, flowering delay is a prominent strategy for avoiding spring frost damage. Our previous study confirmed that treatment with 5% sodium alginate and 100 mM CaCl2 (5AG) to avoid frost damage during the blooming stage delays flowering. To reveal the flowering delay mechanism of peaches, this study systematically analyzed the modification of amino acid profiles in control and 5AG-treated peach plants at different day intervals. Our findings indicate that arginine (Arg), glutamate (Glu), and proline (Pro) levels differed between the control and 5AG-treated peach shoots throughout the phenological development of flower buds. Furthermore, two amino acids (Arg and Glu) are involved in the Pro pathway. Thus, using a computational metabolomics method, Pro biosynthesis and its characteristics, gene ontology, gene synteny, cis-regulatory elements, and gene organizations were examined to decipher the involvement of Pro metabolism in peach flowering delay. In addition, qRT-PCR analysis revealed the transcriptional regulation of Pro-related and flowering-responsive genes and their role in flowering delay. Overall, this pilot study provides new insights into the role of Pro in the flowering delay mechanisms in Prunus persica through 5AG treatment.